POLEMIK PASAL 3 UU NO. 31 TAHUN 1999 TENTANG TIPIKOR MENGENAI UNSUR NIAT JAHAT DAN MEMPERKAYA DIRI BAGI PELAKU TINDAK PIDANA KORUPSI - Berlian Tarigan (Universitas Quality, 2020)
The Constitutional Court (MK) has received a request for judicial review of Article 2 and Article 3 of Law No. 31 of 1999 concerning Eradication of Criminal Acts of Corruption (Corruption Act) as amended by UUNo. 20 of 2001, through Decision No. 25 / PUU-XIV / 2016. In that decision, the Constitutional Court stated that the phrase